1998
DOI: 10.1093/genetics/148.1.479
|View full text |Cite
|
Sign up to set email alerts
|

A High-Density Rice Genetic Linkage Map with 2275 Markers Using a Single F2 Population

Abstract: A 2275-marker genetic map of rice (Oryza sativa L.) covering 1521.6 cM in the Kosambi function has been constructed using 186 F2 plants from a single cross between the japonica variety Nipponbare and the indica variety Kasalath. The map provides the most detailed and informative genetic map of any plant. Centromere locations on 12 linkage groups were determined by dosage analysis of secondary and telotrisomics using >130 DNA markers located on respective chromosome arms. A limited influence on meiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 699 publications
(31 citation statements)
references
References 54 publications
1
28
0
2
Order By: Relevance
“…5 . The linkage map was compared side-to-side with a restriction fragment length polymorphism (RFLP) marker-based high-density linkage map ( Harushima et al 1998 ), in which some markers have been sequenced. Based on the Nipponbare genome sequence (Os-Nipponbare-Reference-IRGSP-1.0) ( Kawahara et al 2013 ), DNA markers located near each other on Nipponbare pseudomolecules are connected with dotted lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 . The linkage map was compared side-to-side with a restriction fragment length polymorphism (RFLP) marker-based high-density linkage map ( Harushima et al 1998 ), in which some markers have been sequenced. Based on the Nipponbare genome sequence (Os-Nipponbare-Reference-IRGSP-1.0) ( Kawahara et al 2013 ), DNA markers located near each other on Nipponbare pseudomolecules are connected with dotted lines.…”
Section: Resultsmentioning
confidence: 99%
“… Linkage map showing the location of xa20 on chromosome 3. A and B show RFLP framework map of chromosome 3 modified from Harushima et al (1998) ; C represents linkage map of xa20 gene constructed from F 2 population from IKC3 and XM6 ( n = 299). DNA markers located near each other on Nipponbare pseudomolecules are connected by dotted lines.…”
Section: Figmentioning
confidence: 99%
“…Several saturated genetic linkage maps based on molecular markers have been developed for rice, using indicaxjapoaica or O. sativaxo. lorzgistantiizata crosses (Causse et al 1994;McCouch et al 1988;Harushima et al 1998). However, no extended linkage study has so far been reported between the two cultivated rice species; only linkage studies on small portions of the genome have been carried using morphological markers (Sano 1990).…”
Section: Introductionmentioning
confidence: 99%
“…A fosmid library constructed from BIL680 was screened with two DNA markers, C213 and C728 (Table S2; Harushima et al., 1998). Consequently, four clones (Fos1, 2, 10 and 12) were identified.…”
Section: Resultsmentioning
confidence: 99%